Absolute and Relative Bioavailability of Oral Solid Dosage Formulations of Deucravacitinib in Humans - Chimalakonda, Anjaneya; Li, Wenying; Marchisin, David; He, Bing; Singhal, Shalabh; Deshpande, Prashant; Brown, Jonathan; Aras, Urvi; Murthy, Bindu (Clinical pharmacology in drug development, 2023)
Deucravacitinib is an oral, selective, allosteric inhibitor of tyrosine kinase 2, an intracellular signaling kinase involved in the pathogenesis of immune‐mediated inflammatory diseases. The absolute and relative bioavailability (BA) were evaluated in phase 1, open‐label studies in healthy adults to assess (1) the absolute BA of the deucravacitinib tablet formulation following single oral administration of a 12‐mg tablet and an intravenous microdose infusion of 0.1‐mg carbon‐13 and nitrogen‐15–labeled deucravacitinib ([ 13 C 2 , 15 N 3 ] deucravacitinib) solution in 8 subjects, and (2) the relative oral BA of deucravacitinib tablet and capsule formulations at the 3‐ and 12‐mg dose levels in 20 subjects. The absolute oral availability of deucravacitinib in the tablet formulation was near complete at approximately 99%. The total clearance (254 mL/min) was low relative to hepatic blood flow, and volume of distribution (∼140 L) was greater than total body water, indicating extravascular distribution. Deucravacitinib systemic exposure (maximum plasma concentration, area under the plasma drug concentration curve from time zero to the time of the last quantifiable nonzero concentration, and area under the plasma drug concentration–time curve from time zero extrapolated to infinity) after administration of the tablet formulation were similar to the capsule at the tested 3‐ and 12‐mg doses. In both studies, deucravacitinib was safe with no clinically relevant changes in laboratory values, electrocardiogram parameters, or vital signs.